(untitled) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the marketing strategies used by Kedai Bikang and Pukis Pekalongan in maintaining business existence as well as the factors that encourage and hinder the implementation of marketing strategies that have been set by Kedai Bikang and Pukis Pekalongan. This research method is descriptive research with a qualitative approach. Data was collected by using observation, interview and documentation techniques. Researchers used triangulation of sources and methods to check the validity of research data. Data analysis in this study uses three components consisting of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the marketing strategy set by Kedai Bikang and Pukis is related to product, price, location. The products sold are very varied and Bikang and Pukis shops are still trying to innovate to add product variants needed by consumers.